LITERATUR REVIEW FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DI KOTA SURABAYA (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to find out the shortcomings and gaps in research on the factors that affect PBB taxpayers in the city of Surabaya and provide conclusions at the end of the study. In this study, researchers found several journals related to taxpayer compliance and the factors that influence tax compliance with inconsistent results. The type of research in this study used the Literature Review method. In this study, the researchers started the process of identifying research related to taxpayer compliance and the factors that influence it by searching for several journals through Google Scholar, whose research was in the city of Surabaya, and found 9 journals from 9 journals with inconsistent research results. For example, the variable understanding of taxes, tax witnesses, and income when examined by one researcher has an effect on tax compliance, and when examined by other researchers there is no effect on tax compliance